A Pedagogical Approach to Integrative Neuromuscular Training to Improve Motor Competence in Children: A Randomized Controlled Trail - Font-Lladó, Raquel; López-Ros, Víctor; Montalvo, Alicia M; Sinclair, Graham; Prats-Puig, Anna; Fort-Vanmeerhaeghe, Azahara (Journal of strength and conditioning research, 2020)
Font-Lladó, R, López-Ros, V, Montalvo, AM, Sinclair, G, Prats Puig, A, and Fort-Vanmeerhaeghe, A. A pedagogical approach to integrative neuromuscular training to improve motor competence in children: a RCT. J Strength Cond Res 34(11): 3078-3085, 2020-To assess the effectiveness of a pedagogical approach to an integrative neuromuscular training (INT) program as a warm-up in physical education (PE) lessons in healthy children: (a) to improve the level of motor competence (MC) and (b) to master fundamental motor skills (FMS) patterns, considering the baseline MC level and the time spent when performing different motor tasks. One hundred ninety students (7.43 ± 0.32 years; 52% girls) were included in this randomized controlled trail and grouped up according to MC basal levels (L1-L4). Motor competence and FMS patterns (CAMSA protocol) were assessed before and after the intervention in a group-based INT warm-up (n = 97) and a group-based conventional warm-up (n = 93). The INT program improved MC (p < 0.001; d = 0.71) and FMS (p < 0.001, d = 0.52). The independent predictors of MC change were: baseline MC level (β = -196; p < 0.012), time spent to perform the task (β = -0.235 p < 0.003), and participation in the INT program (β = 0.201; p < 0.005), explaining 71% of its variability. The INT warm-up shows correlations between improvements in MC in relation to time reduction (L1 p = 0.016, d, L2 p = 0.001, and L4 = 0.001) and FMS patterns (L1 p < 0.001, L2 p < 0.003, L3 p < 0.005, and L4 < 0.001) Moreover, only L3, it showed correlation between changes in time and FMS mastery (p = 0.001). Our results showed that a pedagogical approach to an INT program developed as a warm-up in primary school PE lessons can improve MC and FMS patterns in all subjects, independent of the initial MC level. More interestingly, only in L3, the improvement in MC can be explained by the balance in time required to perform the task and the level of improvement in FMS patterns.